Some Recent American Progress In The Assay Of Copper-Bullion. (041a2e9c-0fea-4a37-b8e1-b7440fca176e) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1913)
Discussion of the paper of Edward Keller, presented at the Butte meeting, August, 1913, and printed in Bulletin No. 80, August, 1913, pp. 2093 to 2115. GEORGE L. HEATH, Hubbell, Mich.:-In the admirable paper quoted, is mentioned the date when the 5-g. assay was first proposed is a standard for refined metal. The author omitted, however, to mention a later paper,1 which contains a proposal for the use of a single " stock solution " of mixed acids, which has been adopted by the American Brass Co. and others. The suggestion is made that such a scheme would save time and manipulation with converter metal. Unless the low current of 0.5 ampere and the large excess of nitric acid, recommended by Mr. Keller, have been proved necessary to hold up antimony-and selenium, the use of the mixed solution which we have adopted will permit the use of 1 ampere of current per square decimeter of cathode surface, until the solutions have become colorless. At this point, we wash the covers and reduce to 0.5 ampere to prevent oxidation or contamination. The ordinary split electrodes have been used. With strong current, at least, the use of an excess of nitric acid tends to the neutralization of the solution before the end of the period, from the formation of too much ammonia., and this is detrimental. Antimony deposits more easily than arsenic, and tends to drag the latter dorm with it. There must, be some such explanation for the fact. that we have made hundreds of deposits of pure cathodes from Lake material containing no antimony, but as. high as 0.5 per cent. of arsenic. By placing an assay beaker in the Frary solenoid, or rotary device, a cathode deposit with less than 0.01 per cent. of impurity is easily obtained in one operation from 3 g. of whitneyite, carrying from 7 to 10 per cent. of arsenic. In such a case, it is necessary to test several times for end point and remove the plate as soon as no brown tint appears (at once) when hydrogen sulphide water is added to the test portion on the spot plate. Edward Keller's proportion,, of solvent figure out as 14 cc. of strong nitric to 11.4 cc. of sulphuric acid (1.84).